Pencegahan Anemia Berbasis Kearifan Lokal Pada Masyarakat Permukiman Sungai di Kecamatan Aluh-Aluh, Kabupaten Banjar, Kalimantan Selatan - Sudjatmiko Setyobudihono; Yuseran Yuseran; Noor Ridha Yanti; Ermina Istiqomah (Universitas Lambung Mangkurat, 2023)
Continuing nutritional problems and stunting can become an inhibiting factor in national development. Community knowledge, attitudes, and skills in processing food sources, especially local food sources, are still very lacking. The opinion that nutritious food is expensive so that they prioritize economic reasons and ignore health problems, is still common in society. A local wisdom-based approach is an important strategy so that people can be aware of the capabilities of food sources and the environment around them and are able to process them into nutritious food sources. The aim of community service is to create nutritional cadres to prevent anemia who have the ability to understand the potential of local food sources and can process them simply as a source of nutritious food, easy to obtain and cheap, especially for river settlement communities in South Kalimantan. Community service activities are carried out in Aluh-Aluh District which is one of the locus of stunting villages in 2022. Thorough identification using an in-depth interview approach is used to find out various matters related to health knowledge, especially anemia symptoms. By utilizing counseling from sources who understand local wisdom and food sources to prevent anemia, it is hoped that more knowledge will be created about local food resources that are useful for preventing anemia. Approaches to adolescents with counseling are expected to be able to encourage additional knowledge and positive attitudes and be able to utilize local food sources independently.